Low temperature, high conductivity Al-doped ZnO film fabrication using modified facing target sputtering - Kim J. (Elsevier, 2015)
© 2015 Elsevier B.V. Al-doped ZnO films were deposited and characterized for a transparent electrode. To synthesize low temperature and low resistivity films using stronger plasma confinement, modified facing target sputtering was used. The modified process was designed using 2-D magnetic field simulation to obtain a uniform magnetic field above the target area. Hydrogen and oxygen gases were added to the sputtering gas in sequence for high quality film fabrication. As a result, 7.14 × 10-4 Ω·cm resistivity film having 6.8 × 1020 cm-3 carrier density, 12.78 cm2/V·s mobility, and 83% optical transmittance of 200-nm thickness was obtained. The process temperature was 70 °C with a relatively high deposition rate of 36 nm/min. The optical emission spectroscopy revealed that the modified facing target sputtering system excited significantly more sputtering species than that of the conventional process. Thus, this process might enable fabrication of the desired film with a higher deposition rate even at a low process temperature. Moreover, little hydrogen gas input can improve both the mobility and carrier density, but excess input sharply degrades the crystallinity and the resistivity of the film.